Integrative religious education in Europe : a study-of-religions approach - Alberts, Wanda (Religion and reason ;, 2007)
This book is a contribution to the development of the young discipline of the didactics of the Study of Religions (Religionswissenschaft) in international perspective. Integrative religious education refers to education about different religions in classrooms with children of various religious and non-religious backgrounds. Cornerstones of recent debates about theory and methodology in the academic study of religions and in education are discussed in the first chapter. They form the basis of the following analysis and evaluation of current approaches to integrative religious education in Europe, with a special focus on England and Sweden. Particular attention is paid to the different underlying concepts of religion, education and ways of representing religious plurality in these approaches. Building on a discussion of the current situation of teaching and learning about religions in schools in Europe in the context of wider cultural, social and political debates, the book concludes with the suggestion of a framework for integrative religious education in Europe, from a perspective that combines insights from the study of religions and education.